2021
DOI: 10.1021/acsami.1c16366
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of a Cubic Porphyrin-Based Covalent Organic Framework for Combined Breast Cancer Therapy

Abstract: A cubic porphyrin-based covalent organic framework (COF) named CTP with excellent hydrophilicity was prepared with a facile method for the first time. Different from the conventional methods for the synthesis of porphyrin-based COFs, this facile strategy has greatly shortened the reaction time under mild conditions. Linking the porphyrin monomer into the COF overcame its poor solubility and biocompatibility and also narrowed the band gap owing to the formation of the π-conjugation structure. The improved bioco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Diminished generation abilities were also observed in the same experiments using HHTP and TFPN (Figure S12). Therefore, the exceptional 1 O 2 generation ability originates from the novel crystalline framework of COF-316 m , coupled with US, which is comparable to porphyrin-based MOF and COF sonosensitizers. , To verify the structural maintenance of COF-316 m after US irradiation, PXRD and IR data were collected (Figure S13). There were no significant differences between before and after US irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diminished generation abilities were also observed in the same experiments using HHTP and TFPN (Figure S12). Therefore, the exceptional 1 O 2 generation ability originates from the novel crystalline framework of COF-316 m , coupled with US, which is comparable to porphyrin-based MOF and COF sonosensitizers. , To verify the structural maintenance of COF-316 m after US irradiation, PXRD and IR data were collected (Figure S13). There were no significant differences between before and after US irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these advantages and potentials, COFs have not yet been reported to generate both types of ROS under US irradiation except only a minority of porphyrin-based COFs. 32 Furthermore, COFs have not been exemplified to activate PMS without metal ions or auxiliary supports. To the best of our knowledge, there are no examples of porous materials that can act simultaneously as sonosensitizers and PMS activators.…”
Section: •−mentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 The absorption region can be extended to near-IR through modification of the porphyrin ligand and tailoring of the structure. 23,24 In this context, metalloporphyrinphosphonate MOFs or CPs are promising candidates because they show not only a broad absorption region but also high water and thermal stability. Recently, we found that the absorption bands of a highly stable 3D Zr-MOF based on 5,10,15,20tetrakis(p-phenylphosphonic acid)-porphyrin (H 10 TPPP) approached ca.…”
Section: ■ Introductionmentioning
confidence: 99%
“…COF is composed of C, H, O, and N light elements, avoiding the potential heavy metal risk brought by metal elements. [3] The large and regular structure also facilitates the diffusion of reactive oxygen species (ROS) from the interior to the surface of the COF. Imine-bridged COFs are generally responsive to acidic conditions and are potential biodegradable carriers in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%